KELIMPAHAN POPULASI Moina macrocopa DIPERTAHANKAN DALAM MEDIA KULTUR MASSA DITAMBAHKAN TEPUNG SPIRULINA PLATENSIS - Redha, El; Fauzana, Noor Arida; Akbar, Junius; Rukmini, Rukmini (EnviroScienteae, 2024)
The purpose of the research was to evaluate the response of the population abundance of Moina macrocopa to the addition of Spirulina platensis flour into mass culture media. In this research, each added 0 mg/day (control), 500 mg/day, 750 mg/day of  Spirulina platensis, as well as the treatments being tested. As a control, dry manure was used. This research was conducted at the Wet Laboratory (wet lab.) Faculty of Fisheries and Marine, Lambung Mangkurat University Banjarbaru. As an experimental container (experimental unit) were 12 aquariums measuring 45 x 25 x 30 cm. In this research, an experimental design was applied, namely Completely Randomized Design (CRD). Statistical testing using Test F or ANOVA with a significant level of 5% and 1%. The further statistical analysis used for the significant treatment calculated F value was Duncan's Test (DMRT). The results showed that at the peak of the abundance of Moina macrocopa (day 21), the highest population was in treatment B = 708 ind/liter, followed by treatment C=535.33 ind and treatment A=70.66 ind/liter. The results of statistical tests (ANOVA) showed that there was no significant difference (F < Ftable 0.05) in the abundance of Moina macrocopa in the three mass culture media added with Spirulina platensis flour.